Resilience and opportunity lessons from the U.S. Gulf Coast after Katrina and Rita - Liu, Amy (James A. Johnson metro series, 2011)
"Examines the roles of community grassroots and charitable organizations as well as national, state, and local governments in post-disaster recovery and reform in the education, health care, legal, and political systems and in land use planning. Focuses on rebuilding to achieve more resilient, prosperous, and equitable communities"--Provided by publisher.